Camp Average : double foul - Battle, Craig, 1980- (Owlkids Books, 2021)
Mack and his friends are back for another summer at Camp Avalon, or as they prefer to call it, "Camp Average." A new year means big changes. For the first time ever, the camp is open to girls, and campers aren't required to play sports competitively. As the weeks pass by, the noncompetitive activities mysteriously start to be canceled, and Mack is required to join the basketball team. Mack knows Winston, the overly competitive camp counselor, is behind it all, and he is determined to save the summer. As Winston pits the girls against the boys to find the best players for the inter-camp basketball tournament, Mack is put in a battle of wits to undermine Winston and preserve the name of "Camp Average."